Evidence for reduced synaptic protein SNAP-25 in cerebrospinal fluid in major depressive disorder and schizophrenia - Patrick Oeckl; Petra Steinacker; Markus Otto; Steffen Halbgebauer; MHD Rami Al Shweiki; Samir Abu-Rumeileh; Naguib Mechawar; Carlos Schönfeldt-Lecuona; Lorenzo Barba; Leonie Werner; Alexander Tarabuko; Ilyas Al-Ali; et al. (BMJ Mental Health)
Background Decreased cerebrospinal fluid (CSF) levels of synaptic proteins, possibly reflecting impaired synaptic function, have been observed in major depressive disorder (MDD).Objective To investigate the diagnostic utility of the soluble N-ethylmaleimide-sensitive-factor attachment receptor (SNARE) complex protein, synaptosomal-associated protein of 25 kDa (SNAP-25), for MDD.Methods Overall, 208 participants with one of MDD, schizophrenia (SCZ) or bipolar disorder (BD), and healthy controls (HCs) were retrospectively enrolled. CSF levels of SNAP-25 were assessed relative to MDD characteristics and the diagnostic potential was analysed. In subgroups of patients, CSF levels of presynaptic neurexin 3 (NRXN3), postsynaptic neurogranin (NRGN) and Alzheimer’s disease biomarkers were measured for comparison.Findings SNAP-25 levels, but not the levels of the other synaptic markers, were significantly decreased in MDD compared with HCs, allowing for discrimination with 68% sensitivity and 67% specificity. SNAP-25 was not associated with MDD severity or antidepressant medication. Compared with HCs, SCZ also displayed decreased SNAP-25 enabling discrimination with 64% sensitivity and 77% specificity. There were strong correlations between levels of synaptic proteins and established Alzheimer pathology markers, with subtle differences in the association pattern between disorders.Discussion Our data suggest that SNAP-25, NRXN3 and NRGN versus beta-amyloid and phosphorylated tau protein 181 (ptau) are regulated differentially across psychiatric disorders and that SNAP-25 has a moderate diagnostic potential for MDD and SCZ. We propose that CSF SNAP-25 level might represent an integrated readout of reduced synaptic function, rather than of synaptic degeneration, in MDD. Further studies are needed to analyse whether this potential can be increased by using multimarker measurements and whether it will be possible to subtype psychiatric disorders according to synaptic involvement in pathophysiology.Clinical implications SNAP-25 and other synaptic proteins in CSF might aid diagnosis and subtyping of MDD and SCZ. The current development of sensitive methods to also determine synaptic proteins in blood samples from patients will advance the validation of the biomarker potential and contribute to understanding of synaptic involvement in the pathophysiology of MDD and SCZ.